The Challenges of Teaching Islamic Education In the Millennial Generation Era - Fathuddin, Fauziah; Nurdin, Nurdin; Rustina, Rustina (Department of Islamic Education, Postgraduate Program Univercity for Islamic Studies Palu, 2023)
This article discusses the issues of Islamic religious education learning in the millennial era, focusing on teachers, teaching methods, learning media, and students' interest in learning. The research was conducted in a high school in the Pasangkayu district. The research utilized a qualitative method with data collection techniques such as direct observation, in-depth interviews, and document analysis. The research findings indicate that implementing Islamic religious education learning in the millennial generation begins with preparing teaching tools. However, the application of teaching methods and the utilization of educational technology still need more improvement. The issues of Islamic religious education learning in the millennial generation in high school include internal and external problems. Internal problems include the teachers' need for more ability to deliver the lessons and utilize educational technology. Islamic religious teachers must be role models for students regarding responsibility, low interest, and learning motivation. External problems include the influence of scientific and technological advancements in communication and the impact of social environments. The solutions to these learning problems involve Islamic religious teachers improving the learning process, providing learning aids, and mastering educational technology. Additionally, teachers engage in discussions with various stakeholders at the school to address the learning issues.